Different Expression of Aldehyde Dehydrogenases 1A1 and 2 in Oral Leukoplakia with Epithelial Dysplasia and in Oral Squamous Cell Carcinoma - Herrera Costa, Fernanda [UNESP]; Narana Ribeiro El Achkar, Vivian [UNESP]; Costa, Victor [UNESP]; Paladini, Isabela [UNESP]; Kowalski, Luiz Paulo; Rodarte Carvalho, Yasmin [UNESP]; Kaminagakura, Estela [UNESP] (Wolters Kluwer, 2019)
Oral potentially malignant disorders (OPMD) may develop malignant characteristics and transform into oral squamous cell carcinoma (OSCC) in a range of 1% to 2% of cases. Chronic alcohol consumption is associated with carcinogenesis, but its mechanism has not yet been fully elucidated. ALDH1A1 and 2, isoenzymes responsible for aldehyde oxidation involved in ethanol metabolism may be associated with the development of malignant head and neck neoplasms. The aim of this study was to analyze the expression of ALDH1A1 and ALDH2 in oral leukoplakia with epithelial dysplasia (OLP) and OSCC. A retrospective study was conducted on 27 cases of OLP and 30 cases of OSCC. Clinical data were obtained from medical records, and all cases were classified as mild, moderate, and severe for OLP, and well-differentiated, moderately differentiated, or poorly differentiated for OSCC cases. The ALDH1A1 and ALDH2 expression in OLP and OSCC was evaluated by the immunohistochemical technique. There was predominance of the male sex, in both OLP and OSCC cases. Oral tongue was the most affected site in both groups. OLP showed positive protein expression of ALDH1A1 in all cases, both basal and suprabasal epithelial layers, whereas ALDH2 showed less protein expression. In OSCC, the immunohistochemical reaction for ALDH1A1 expression was negative in 70%, whereas ALDH2 expression was positive in all cases. This study demonstrated the gradual loss of ALDH1A1 expression in OSCC in comparison with OLP, and the increased ALDH2 expression in OSCC.
Keywords: alcohol; immunohistochemistry; isoenzymes; oral cancer; squamous cell carcinoma